Rural Development Strategy: 1990s Context and Constraints - Vail, David; Hillard, Michael (Maine Policy Review, 1996)
In this comprehensive article on rural economic development, David Vail and Michael Hillard describe key trends and past changes which are shaping rural America’s—and in particular, rural Maine’s—economic future. They conclude with seven hypotheses about rural Maine’s socioeconomic crisis, and call for the development of a state-level strategy for rural development that fully accounts for Maine’s varied resources, geography, and opportunities.